2021
DOI: 10.1016/j.cmi.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Congenital infection of SARS-CoV-2 in live-born neonates: a population-based descriptive study

Abstract: Objective This study aimed to evaluate the evidence of mother-to-child transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Methods This is a descriptive, multicenter, observational study in nine tertiary care hospitals throughout Spain. The study population was women with COVID-19 during pregnancy. Mother-to-child transmission was defined as positive real-time reverse-transcriptase-polymerase-chain-reaction (RT-PCR) of SARS-CoV-2 in amniotic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The prevalence of placental infection in COVID-19-positive women is low (7.7–21%) [ 73 ]⁠.A few studies have demonstrated SARS-CoV-2 placental infection diagnosis by ISH, IHC, RT-PCR, and transmission electron microscopy (TEM) [ 11 , 15 , 31 , 34 , 52 , 53 , 58 , 61 , 62 , 64 , 65 , 67 , 71 , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] ]⁠. Viral RNA, proteins, and particles were mainly localized in the syncytiotrophoblasts [ 52 , 58 , 61 , 62 , 64 , 80 , 81 , 86 ]⁠.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of placental infection in COVID-19-positive women is low (7.7–21%) [ 73 ]⁠.A few studies have demonstrated SARS-CoV-2 placental infection diagnosis by ISH, IHC, RT-PCR, and transmission electron microscopy (TEM) [ 11 , 15 , 31 , 34 , 52 , 53 , 58 , 61 , 62 , 64 , 65 , 67 , 71 , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] ]⁠. Viral RNA, proteins, and particles were mainly localized in the syncytiotrophoblasts [ 52 , 58 , 61 , 62 , 64 , 80 , 81 , 86 ]⁠.…”
Section: Resultsmentioning
confidence: 99%
“…Positive IgA or IgM serology and positive RT-PCR of sterile samples [ 109 ]⁠. A few confirmed cases of in utero transmission of SARS-CoV-2 have been reported in the literature [ 15 , 53 , 64 , 91 ]⁠. SARS-CoV-2 infection of the placenta does not always translate to vertical transmission but may cause placenta insufficiency and pathology, resulting in perinatal morbidity and mortality without infection [ 72 , 90 ]⁠.…”
Section: Resultsmentioning
confidence: 99%
“…It results in still birth, cerebral palsy, brain infarcts and hypoxic ischemic encephalopathy. (12) Congenital COVID-19 was reported to be silent or cause respiratory distress, and in less than 3% cause severe pneumonia (13). It was also reported to cause miscarriage, preterm labor, and fetal demise (14).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study of women infected late in pregnancy, SARS-CoV-2 viral RNA was detected in 23 out of 54 placentas [50]. Nevertheless, while vertical transmission of SARS-CoV-2 from mother to child has been described, it appears to be exceedingly rare [51][52][53][54][55][56][57][58]. Long-term neurodevelopmental outcomes of infants who were exposed to SARS-CoV-2 in utero remains an area for future targeted studies [59][60][61].…”
Section: Maternal To Fetal Transmission Of Severe Acute Respiratory S...mentioning
confidence: 99%